CONSTRUCTION GRAMMAR AND ENGLISH LANGUAGE TEACHING - Lionel Wee (Universitas Katolik Indonesia Atma Jaya, 2007)
This paper begins by noting that disappointments have been expressed with the communicative approach to language teaching, before discussing a number of problems involved in its implementation. This leads to the question of how English language teaching can attend to grammatical form, but without sacrificing the focus on communicative function. The paper then points to a convergence between strands of research in both theoretical and applied linguistics. In theoretical linguistics, the increasing prominence of ‘construction grammars’ resonates nicely with recent suggestions that ‘lexical phrases’ or ‘formulaic sequences’ should be given greater focus in language teaching. The rest of the paper goes on to consider the pedagogical value of the notion of a construction. Keywords: Communicative approach, construction grammar, formulaic language, workplace communication